Macroeconomic imbalances and institutional reforms in the EMU - Stefan Ederer (WWWforEurope, 2015)
The paper summarises the channels and mechanisms which lead to the emergence of macroeconomic imbalances in the EMU before, in and after the crisis of 2008/09. It focuses on the role of the specific institutional setting of the EMU in these developments and outlines the key reforms which are necessary to eliminate the imbalances and prevent them from re-emerging.
Keywords: E02; E52; E62; F32; F33; F42; 330; EMU; macroeconomic imbalances; European economic policy